Substrate Optimization for Bioemulsification Using Saccharomyces cerevisiae 2031 by Response Surface Methodology - Justine Allen S. Malabuyoc; Virgie A. Alcantara; Rhebner E. Arocena; Francisco B. Elegado (Agro Bali : Agricultural Journal, 2023)
Biosurfactants are microbially derived amphiphilic molecules that can be used as biodegradable emulsifiers in various applications. For biosurfactant production to be economically viable, inexpensive raw materials should be used. In this study, substrate optimization of biosurfactant production from Saccharomyces cerevisiae 2031 was done using molasses as an additional carbon source to glucose, and coco paring meal extract as a nitrogen source. Optimum conditions were determined as pH 5.69, 10.60% (w.v-1) molasses and 7.27% (v.v-1) coco paring meal extract using Box-Behnken design. At these conditions, the obtained responses: namely biomass concentration and % emulsification index determined with kerosene, were 6.43 g.L-1 and 82.81%, respectively. The highest emulsification activity (84.60%) was attained after 4 days of shake-flask fermentation. On the other hand, a bioreactor system observed the maximum yield for emulsification activity (93.33) after 4 days. The biosurfactant extracted was characterized by its total sugar, protein content and surface tension reduction.